Indigenous arbuscular mycorrhiza and Trichoderma from systems with soybean predominance can improve tomato growth - Commatteo, Jacqueline Giselle (2019)
In the last decades, there has been a tendency towards sustainable agriculture. Following this trend, edaphic fungi as Trichoderma and arbuscular mycorrhizal fungi (AMF) could increase plant growth contributing to diminish agricultural chemical supply. However, little information exists in current research regarding the possible effects of alternative practices to soybean monoculture systems on fungal groups that could contribute to plant health and/or productivity. Thus, our objective was to assess changes in the abundance and diversity of indigenous AMF and Trichoderma from a long-term field experiment located in the Argentinean Pampas, in order to test the effect of alternative practices to soybean monoculture. The fungal ability to promote the growth of crops, such us tomato plant was also tested. Soil samples were collected from a soybean monoculture system (Sb), a system including cover crop (Avena sativa) followed by soybean (CC/Sb) and a system including rotations (rot) of Soybean-Maize-Wheat crops CC/Sb-rot, M-rot and W-rot, respectively. Highest AMF and Trichoderma abundance was found at W-rot and M-rot systems, and highest AMF diversity was found at W-rot and CC systems. Furthermore, highest mycorrhizal colonization was found at CC/Sb and W-rot systems. Inoculated plants with single AMF consortium or with Trichoderma strains showed significant increases in comparison with the control. Dual inoculation increased tomato plant growth as compared to the control, and evidence of synergism was found by increases in shoot and root growth. Our results show that dual inoculation with indigenous AMF and Trichoderma from alternative crop systems to soybean monoculture could play an important role in tomato plant growth. This information could be useful to decrease production costs and environmental impacts.